THE INFLUENCE OF LEADERSHIP STYLE AND COMPENSATION ON EMPLOYEE PERFORMANCE AT PT. XYZ - Fajrin, Yeni; Putrie, Rena Augia; Zain, Muhammad Ja’farullah; Julianti, Tiara Alvina; Amalia, Yuni Putri (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2024)
This research aims to determine the influence of leadership style and compensation on employee performance at PT. XYZ. Quality human resources are human resources who have high competence and skills that can advance the company because human resources greatly influence the economic development of a local and global company. That is why leadership style and compensation are important factors in human resource management because they will influence employee performance in a company. This research uses qualitative methods and literature study techniques. The results of research at PT XYZ show that Leadership Style and Compensation have a positive effect on employee performance. If the leadership style and compensation program are felt to be fair and competitive by employees, then it will be easier for the company to attract potential employees, retain them, and motivate employees to improve their performance further. If these two things can be fulfilled, then employees will feel satisfied. Satisfaction will trigger employees to continue to improve their performance when employees have high motivation, employees can optimize their abilities at work so that company goals and employee needs will be achieved together. However, if the leadership style and compensation are deemed unfair and unsatisfactory for employees, then employee performance will decline and ultimately affect the company's productivity.